Whole-cell phenotypic screening of medicines for malaria venture pathogen box identifies specific inhibitors of plasmodium falciparum late-stage development and egress - Patra, Alok Tanala; Hingamire, Tejashri; Belekar, Meenakshi A.; Xiong, Aoli; Subramanian, Gowtham; Bozdech, Zbynek; Preiser, Peter; Shanmugam, Dhanasekaran; Chandramohanadas, Rajesh (Antimicrobial Agents and Chemotherapy, 2020)
We report a systematic, cellular phenotype-based antimalarial screening of the Medicines for Malaria Venture Pathogen Box collection, which facilitated the identification of specific blockers of late-stage intraerythrocytic development of Plasmodium falciparum. First, from standard growth inhibition assays, we identified 173 molecules with antimalarial activity (50% effective concentration [EC50] <= 10 mu M), which included 62 additional molecules over previously known antimalarial candidates from the Pathogen Box. We identified 90 molecules with EC50 of <= 1 mu M, which had significant effect on the ring-trophozoite transition, while 9 molecules inhibited the trophozoite-schizont transition and 21 molecules inhibited the schizontring transition (with >= 50% parasites failing to proceed to the next stage) at 1 mu M. We therefore rescreened all 173 molecules and validated hits in microscopy to prioritize 12 hits as selective blockers of the schizont-ring transition. Seven of these molecules inhibited the calcium ionophore-induced egress of Toxoplasma gondii, a related apicomplexan parasite, suggesting that the inhibitors may be acting via a conserved mechanism which could be further exploited for target identification studies. We demonstrate that two molecules, MMV020670 and MMV026356, identified as schizont inhibitors in our screens, induce the fragmentation of DNA in merozoites, thereby impairing their ability to egress and invade. Further mechanistic studies would facilitate the therapeutic exploitation of these molecules as broadly active inhibitors targeting late-stage development and egress of apicomplexan parasites relevant to human health.
Keywords: DNA fragmentation; egress; Medicines for Malaria Venture; MMV; Pathogen Box; phenotypic screening; Plasmodium falciparum; schizonts; stage-specific inhibition